The three-dimensional context of a double helix determines fluorescence of the internucleoside-tethered pair of fluorophores - Metelev, Valeri (2013)
We report a general phenomenon of the formation of either a fluorescent, or of an entirely quenched oligodeoxynucleotide (ODN) duplex system by hybridizing pairs of complementary ODNs with identical chemical composition. The ODNs carried internucleoside tether-linked cyanines, where the cyanines were chosen to form a Förster's resonance energy transfer (FRET) doner/acceptor pair. The fluorescent and quenched ODN duplex systems differed only in that the cyanines linked to the respective ODNs s were linked either closer to the 5′-, or closer to the 3′-ends of the molecule. In either case however, the dyes were separated by an identical number (7 or 8) of base pairs. Characterization by molecular modeling and energy minimization using a conformational search algorithm in a molecular operating environment (MOE) revealed that linking of the dyes closer to the 5′-ends resulted in their reciprocal orientation across the major groove which allowed a closely interacting dye pair to be formed. This overlap between the donor and acceptor dye molecules resulted in changes of absorbance spectra consistent with the formation of H-aggregates. Conversly, dyes linked closer to 3′-ends exhibited emissive FRET and formed a pair of dyes that interacted with the DNA helix only weakly. Induced CD spectra analysis suggested that interaction with the double helix was weaker than in the case of the closely interacting cyanine dye pair. Linking the dyes such that the base pair separation was 10 or 0 favored energy transfer with subsequent acceptor emission. Our results suggest that when interpreting FRET measurements from nucleic acids, the use of a “spectroscopic ruler” principle which takes into account the 3D helical context of the double helix will allow more accurate interpretation of fluorescence emission.